2021
DOI: 10.1016/j.heliyon.2021.e06982
|View full text |Cite
|
Sign up to set email alerts
|

Evans index among adult Ghanaians on normal head computerized tomography scan

Abstract: Introduction: Normal-Pressure Hydrocephalus (NPH) is a neurological condition which is made up of a clinical triad of gait disturbance, dementia and urinary incontinence and can be reversed by ventricular shunting. Currently, some guidelines suggest the use of Evans' index (EI) for diagnosis of hydrocephalus radiologically. Most of the studies are based on the Western population data. None of these studies have been performed in the Ghanaian population setting yet. The aim of this study was to quantitatively e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…3 However the study in Ghanaians, Nigerians and South Indian population did not show any statistical difference. [6][7][8] The mean values for both sexes are within the normal cutoff of 0.3 for Evan's index in our study.…”
Section: Discussionsupporting
confidence: 52%
“…3 However the study in Ghanaians, Nigerians and South Indian population did not show any statistical difference. [6][7][8] The mean values for both sexes are within the normal cutoff of 0.3 for Evan's index in our study.…”
Section: Discussionsupporting
confidence: 52%
“…Several studies have referred to the positive relationship between aging and ventricular indices changes [3][4][5][11][12][13]. Currà et al [4] investigated three ventricular indices in more than 3,000 brain scans, and reported earlier ventricular enlargement in males than females, and also demonstrated sig- Since the literature review suggests the significance of ventricular symmetry [14,15], it was also investigated in our study.…”
Section: Discussionmentioning
confidence: 76%
“…Several studies have referred to the positive relationship between aging and ventricular indices changes [ 3 - 5 , 11 - 13 ]. Currà et al [ 4 ] investigated three ventricular indices in more than 3,000 brain scans, and reported earlier ventricular enlargement in males than females, and also demonstrated significant changes in Evans, bitemporal, and parieto-occipital indices at the ages of 79, 83, and 87 years, respectively.…”
Section: Discussionmentioning
confidence: 99%